EXCAVATIONS IN THE ROMAN FORUM OF BUTHROTUM (BUTRINT): FIRST TO THIRD CENTURY POTTERY ASSEMBLAGES AND TRADE - R. Hernandez, David; Reynolds, Paul; Çondi, Dhimitër (Rei Cretariae Romanae Fautorum Acta, 2024)
Under the auspices of the Albanian Institute of Archaeology and the Butrint Foundation, excavations undertaken in the civic centre of the ancient city of Buthrotum (modern Butrint) conclusively identified the location of the Roman forum. This paper presents some of the preliminary results of the ceramic research from the Roman Forum Excavations at Butrint.